Answer:
(x + 1)(5x + 2)
Explanation:
5x² + 7x + 2
consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 5 × 2 = 10 and sum = + 7
the required factors are + 5 and + 2
use these factors to split the x- term.
5x² + 5x + 2x + 2 ( factorise the first/second and third/fourth terms )
= 5x(x + 1) + 2(x + 1) ← factor out (x + 1) from each term
= (x + 1)(5x + 2)
since multiplication is commutative, that is a × b = b× a , then
factored form is either
(x + 1)(5x + 2) or (5x + 2)(x + 1)